IDENTIFIKASI JENIS BAKTERI KONTAMINAN PADA TANGAN PERAWAT DI BANGSAL PENYAKIT DALAM RSUD ULIN BANJARMASIN PERIODE JUNI-AGUSTUS 2014 - Ikhwanda Angga L.; Muhammad Darwin Prenggono; Lia Yulia Budiarti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
Nosocomial infection is an infection by viruses , bacterias, and fungal pathogens that attack a patient undergoing treatment at a hospital. The source of nosocomial infections can be derived from one's body own endogenous flora and cross-infection through the hands of health care workers. The aim of this study was to identify the types of contaminants bacterias on the hands of the nurses of Disease Ward at RSUD Ulin Banjarmasin from June to August 2014. This is a descriptive study with cross sectional approach. A total of 26 samples were selected using total sampling method. The results of the nurses' hand swab which had been cultured in an isolation media were viewed using a microscope. Descriptive analysis showed that there were four types of bacteria on the hands of nurses hand swab results: Staphylococcus aureus (53,85%), Staphylococcus epidermidis (34,62%), Escherichia coli (7,69%), and Bacillus sp.(3,84%). Therefore it can be concluded that bacterial contaminants found on the hands of nurses were Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Bacillus sp. Keywords: nosocomial infection, contaminant bacterias, nurses' hand